2020
DOI: 10.1093/ajh/hpaa015
|View full text |Cite
|
Sign up to set email alerts
|

A Variant in the NEDD4L Gene Associates With Hypertension in Chronic Kidney Disease in the Southeastern Han Chinese Population

Abstract: BACKGROUND “Neuronal precursor cell expressed developmentally down-regulated 4-like” (NEDD4L) is considered a candidate gene for hypertension—both functionally and genetically—through the regulation of the ubiquitination of the epithelial sodium channel (ENaC). This study explores the relationship between genetic variation in NEDD4L and hypertension with chronic kidney disease (CKD) in the southeastern Han Chinese population. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…NEDD4-like E3 ubiquitin protein ligase ( NEDD4L ) encodes a member of the Nedd4 family of HECT domain E3 ubiquitin ligases. In humans, NEDD4L is involved in the process of several diseases, including the inhibition of hepatocellular carcinoma cell growth [ 62 ] and involvement in viral replication [ 63 ], while its mutation is associated with hypertension in chronic kidney disease [ 64 ]. Currently, there are no functional studies on this gene in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…NEDD4-like E3 ubiquitin protein ligase ( NEDD4L ) encodes a member of the Nedd4 family of HECT domain E3 ubiquitin ligases. In humans, NEDD4L is involved in the process of several diseases, including the inhibition of hepatocellular carcinoma cell growth [ 62 ] and involvement in viral replication [ 63 ], while its mutation is associated with hypertension in chronic kidney disease [ 64 ]. Currently, there are no functional studies on this gene in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies established the association of NEDD4L with cardiovascular disease. A series of clinical and basic research have demonstrated that NEDD4L is associated with hypertension 17–20 . Our recent work has proved that NEDD4L participated in miR‐30a‐attenuated atherosclerosis 21 .…”
Section: Introductionmentioning
confidence: 90%
“…A series of clinical and basic research have demonstrated that NEDD4L is associated with hypertension. 17 , 18 , 19 , 20 Our recent work has proved that NEDD4L participated in miR‐30a‐attenuated atherosclerosis. 21 Nonetheless, the role of NEDD4L on endothelial cells has yet to be fully illustrated.…”
Section: Introductionmentioning
confidence: 98%